EFFECT OF PARENTAL AND PEER GROUP INFLUENCE ON CAREER CHOICE AMONG SECONDARY SCHOOL STUDENT IN OYO EAST LOCAL GOVERNMENT, NIGERIA - Okunade Joseph Boluwatife,; Anyanwu George, (International Journal of Innovations in Engineering Research and Technology, 2021)
The purpose of this study is directed at finding the effects of parental and peer group influence on career choice among secondary school students in Oyo west local government area of Oyo State. The researchers used a descriptive survey design method. Two hundred students who were randomly selected using simple random sampling procedure were used as respondent for the purpose of the study. The instrument used for the collection of data for this study was a structured questionnaire (PIPQ) and the data collected were analyzed using t-test statistics. Two null research hypotheses were raised and tested for in the body of the work. The findings revealed that parents do influence the career choice of students. Some recommendations were made among which was that counselling programme opportunities should be made available to students.